The reflection of the combination of genotypes of polymorphic loci of COMT VAL158MET and MAOA -uVNTR in psychological features of girls - Mariya V. Bunyaeva; Ekaterina М. Kovsh; Irina А. Skirtach; Aleksandr B. Il'in (Rossijskij psihologičeskij žurnal., 2018)
In recent years, much research on psychological features of carriers of different genes has been done. Studying the role of combinations of various genes in the formation of personal traits is the next step in the understanding of the specificity of the influence of genes on personality traits. The MAOA and COMT genes of the monoaminergic system are the subject of research of psychologists because of their impact on the duration of stay of neurotransmitters-monoamines in the synaptic space, and hence their potential impact on the duration and intensity of emotional reactions. Taking into account the constancy of this influence the authors assumed that these genes could be associated with stable personality characteristics, which was confirmed by not numerous scientific studies. The paper presents the results of the study, which involved 115 girls at the age from 18 to 30. The procedure of genotyping with the discrimination of polymorphic loci of MAOA -uVNTR and COMT Val158Met was the first stage of the experiment. The psychodiagnostic stage included the study of personality traits of the participants: the level of aggression, types of legitimized aggression, types of behavior in the conflict, formal and dynamic properties of individuality, and tendency to various forms of deviant behavior. The results of the study enabled to make psychological portraits of carriers of various combinations of genes. The carriers of the combination of the high-activity forms of the studied genes had the sanguine temperament, high aggression, intellectual speed, and flexibility. The carriers of the combination of the MAOA M heterozygous genotype and the low-activity genotype of AA COMT had the melancholic temperament, low level of aggression, intellectual speed, and flexibility. In the present study the authors made the assumption that the COMT A allele was associated with the tendency to suppression of aggression; the COMT G allele was probably associated with the preference for open forms of aggressive behavior and a high level of general activity. The COMT heterozygous genotype was associated with a low level of aggression; the MAOA L genotype was associated with a high level of aggression.